Planeación de la Auditoria Administrativa (2019)
We study the determination of the course of action to be followed in the development of an Administrative Audit, determining the principles that serve to guide and mark the sequence of operations necessary to carry it out. In the first place, we are going to determine the indispensable research activities for the planning of the Administrative Audit, presenting them in the order that in our opinion is the most logical. First, the preliminary investigation, then previous interviews and as a fundamental part two points that converge in the core of this section the definition of the area to investigate and determination of the details to study.